Evaluation of the P-solubilizing activity of soil microorganisms and its sensitivity to soluble phosphate - O. Mikanová; J. Nováková (Plant, Soil and Environment, 2002)
Microbial solubilization of hardly soluble mineral phosphates in soil is an important process in natural ecosystems and in agricultural soils. Regulation of the P-solubilizing activity by the presence of soluble phosphates in medium was determined. For this reason we decided to test a number of soil bacteria showing a high P-solubilizing activity for its sensitivity to the presence of soluble dihydrogen potassium phosphate in medium. At these studies, the direct determination of the solubilized phosphate in medium was masked by the presence of relatively high concentrations of soluble phosphate added. Therefore, we have modified the method, determining the residual tricalcium phosphate. The effect of soluble phosphate in medium on the P-solubilizing activity of rhizosphere isolates and strains of Rhizobium were tested in liquid cultures with the addition of various concentrations of soluble KH2PO4. The medium was filtered after incubation and the remaining tricalcium phosphate was separated by filtration. Filter papers with the remaining tricalcium phosphate were hydrolysed with 2N H2SO4. Phosphorus was determined spectrophotometrically. The P-solubilizing activity was expressed as a difference between the tricalcium phosphate added and its remainder after the incubation. These results fully confirmed that there exist the strains, whose P-solubilizing activity is inhibited and other strains, whose P-solubilizing activity is not inhibited or is inhibited very little in the presence of soluble phosphate. The use of our adapted method was much more suitable for this type of experiments.